KONTRIBUSI TOL (TAX ON LOCATION) DALAM PEMBANGUNAN EKONOMI DI PALEMBANG - Rendino; Zalima, Mareta; Ikrarudin, Septi Annisa; Amelia, Sinta; Panorama, Maya (JEPP : Jurnal Ekonomi Pembangunan Dan Pariwisata, 2023)
This study examines the contribution of the Toll Road to Palindra's economic development. The Palindra Toll Road, which has an investment value of 3.3 trillion, is mostly built in swampy areas and difficult terrain, so a special construction method is needed, namely by using the Vacuum Consolidation Method (VCM) technology. Roads were conducted to collect data, followed by validation and reliability tests, Critical Performance Analysis (IPA). The construction of the toll road over the swamp resulted in some agricultural land in the Pemulutan area being displaced. This certainly has an impact on the income of farmers whose daily work is farming. In addition, there are many other positive impacts that can be utilized until now, such as toll roads that facilitate access to connect from one area to another, as well as stabilizing traffic that usually occurs in the Palembang- Indralaya area.ABSTRACT This study examines the contribution of the Toll Road to Palindra's economic development. The Palindra Toll Road, which has an investment value of 3.3 trillion, is mostly built in swampy areas and difficult terrain, so a special construction method is needed, namely by using the Vacuum Consolidation Method (VCM) technology. Roads were conducted to collect data, followed by validation and reliability tests, Critical Performance Analysis (IPA). The construction of the toll road over the swamp resulted in some agricultural land in the Pemulutan area being displaced. This certainly has an impact on the income of farmers whose daily work is farming. In addition, there are many other positive impacts that can be utilized until now, such as toll roads that facilitate access to connect from one area to another, as well as stabilizing traffic that usually occurs in the Palembang- Indralaya area.